Lower Doses of Fructose Extend Lifespan in Caenorhabditis elegans. (4th May 2017) - Zheng, Jolene; Gao, Chenfei; Wang, Mingming; Tran, Phuongmai; Mai, Nancy; Finley, John W.; Heymsfield, Steven B.; Greenway, Frank L.; Li, Zhaoping; Heber, David; Burton, Jeffrey H.; Johnson, William D.; et al.
ABSTRACT: Epidemiological studies indicate that the increased consumption of sugars including sucrose and fructose in beverages correlate with the prevalence of obesity, type-2 diabetes, insulin resistance, hyperinsulinemia, hypertriglyceridemia, and hypertension in humans. A few reports suggest that fructose extends lifespan in Saccharomyces cerevisiae. In Anopheles gambiae, fructose, glucose, or glucose plus fructose also extended lifespan. New results presented here suggest that fructose extends lifespan in Caenorhabditis elegans ( C. elegans ) wild type (N2). C. elegans were fed standard laboratory food source ( E. coli OP50), maintained in liquid culture. Experimental groups received additional glucose (111 mM), fructose (55 mM, 111 mM, or 555 mM), sucrose (55 mM, 111 mM, or 555 mM), glucose (167 mM) plus fructose (167 mM) (G&F), or high fructose corn syrup (HFCS, 333 mM). In four replicate experiments, fructose dose-dependently increased mean lifespan at 55 mM or 111 m Min N2, but decreased lifespan at 555 mM ( P < 0.001). Sucrose did not affect the lifespan. Glucose reduced lifespan ( P < 0.001). Equal amount of G&F or HFCS reduced lifespan ( P < 0.0001). Intestinal fat deposition (IFD) was increased at a higher dose of fructose (555 mM), glucose (111 mM), and sucrose (55 mM, 111 mM, and 555 mM). Here we report a biphasic effect of fructose increasing lifespan at lower doses and shortening lifespan at higher doses with an inverse effect on IFD. In view of reports that fructose increases lifespan in yeast, mosquitoes and now nematodes, while decreasing fat deposition (in nematodes) at lower concentrations, further research into the relationship of fructose to lifespan and fat accumulation in vertebrates and mammals is indicated.